Risk factors for postoperative recurrence of desmoid tumors: a retrospective cohort analysis - Peng, Yue; Liu, Shiyao; Li, Yi; Chen, Xiaoyu; Hu, Yuanxin; Du, Guobo (Frontiers in Oncology, 2026)
ObjectiveDesmoid tumors (DTs) are rare soft-tissue neoplasms characterized by local invasiveness and high recurrence potential. Due to heterogeneous clinical behavior and unresolved controversies regarding postoperative recurrence risk factors, optimal management remains challenging. This study aimed to identify predictors of recurrence-free survival (RFS) after grossly complete recection.MethodsWe retrospectively analyzed 81 DT patients undergoing resection at our institution (September 2014–December 2024). Clinicopathological variables were assessed using Cox regression for recurrence risk, with RFS compared via Kaplan-Meier analysis.ResultsThe median follow-up was 55 months (range: 4–127 months). The 1-year, 3-year, and 5-year RFS rates for the entire cohort were 89.8% (95% CI: 83.1-96.5), 73.8% (95% CI: 63.6-84.0), and 65.5% (95% CI: 53.5-77.5), respectively. Univariate Cox regression analysis showed that larger tumor size (per 1 cm increase: HR = 1.271, p < 0.001), recurrent disease status (HR = 2.741, p = 0.027), and tumor location on an extremity (HR = 2.62, p = 0.021) were significantly associated with poorer prognosis. To mitigate the risk of overfitting, the subsequent multivariate analysis was limited to two variables. This model identified both tumor size (HR = 1.283, p < 0.001) and extremity location (HR = 2.899, p = 0.011) as independent risk factors. The robustness of these findings was further confirmed using a Bonferroni correction (adjusted significance level α = 0.025).ConclusionIn this cohort, tumor size and extremity location were identified as independent predictors of worse recurrence-free survival in patients with desmoid tumors following macroscopic complete resection. These robust factors may aid in postoperative risk stratification and inform patient counseling.